Carbon and nitrogen stock and fluxes in coastal Atlantic Forest of southeast Brazil: potential impacts of climate change on biogeochemical functioning - DM Villela; EA de Mattos; AS Pinto; SA Vieira; LA Martinelli (Brazilian Journal of Biology)
The Atlantic Forest is one of the most important biomes of Brazil. Originally covering approximately 1.5 million of km², today this area has been reduced to 12% of its original size. Climate changes may alter the structure and the functioning of this tropical forest. Here we explore how increases in temperature and changes in precipitation distribution could affect dynamics of carbon and nitrogen in coastal Atlantic Forest of the southeast region of Brazil The main conclusion of this article is that the coastal Atlantic Forest has high stocks of carbon and nitrogen above ground, and especially, below ground. An increase in temperature may transform these forests from important carbon sinks to carbon sources by increasing loss of carbon and nitrogen to the atmosphere. However, this conclusion should be viewed with caution because it is based on limited information. Therefore, more studies are urgently needed to enable us to make more accurate predictions.